1983
DOI: 10.14430/arctic2287
|View full text |Cite
|
Sign up to set email alerts
|

Under Landfast Ice

Abstract: The layer of water under landfast ice has unique oceanographic characteristics, as described in this review of recent assessment information for the central Alaskan Beaufort Sea coast. Water circulation is very slow, usually near the lower threshold of current meters. Barometric storms cause infrequent surges of water. The weak thermohaline-driven circulation is the reverse of that in ice-free estuaries. Watertemperatures are always close to the slowly declining freezing point, and salinity gradually increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The microdistribution of these crustaceans in the under-ice habitats varies from species to species (Carey 1985). Individuals have been observed living in brine channels (Cross 1982;Newbury 1983) and partially or fully embedded in the ice (Gulliksen 1984). Green & Steele (1975) reported that Gammaraconrhus loricatus was the only amphipod species associated with ice stalactites and may at times be frozen within them.…”
Section: Introductionmentioning
confidence: 99%
“…The microdistribution of these crustaceans in the under-ice habitats varies from species to species (Carey 1985). Individuals have been observed living in brine channels (Cross 1982;Newbury 1983) and partially or fully embedded in the ice (Gulliksen 1984). Green & Steele (1975) reported that Gammaraconrhus loricatus was the only amphipod species associated with ice stalactites and may at times be frozen within them.…”
Section: Introductionmentioning
confidence: 99%
“…Newbury (21) has published an excellent review of similar observations made during studies of nearshore waters in areas of the Alaskan Beaufort Sea Stefasson Sound). He also reviewed the nearshore thermohaline circulation required to generate the observed conditions along the Beaufort Sea coast.…”
Section: Introductionmentioning
confidence: 99%
“…and in brine channels in the bottom layers of the ice (Cross 1982;Newbury 1983;Gulliksen 1984). These amphipods may vary in size from about 10 to 6Qmm in total length, with Gammarus wilkirzkii being the largest species in the Arctic.…”
mentioning
confidence: 99%